Vector-virus interactions in vesicular stomatitis virus transmission by Culicoides sonorensis midges - Rozo Lopez, Paula Camila (Kansas State University, 2022)
Culicoides biting midges are nuisance pests of livestock and well-known vectors of veterinary arboviruses, such as vesicular stomatitis virus (VSV). Due to the complex virus epidemiology, some of the mechanisms of geographic spread and virus maintenance during interepidemic periods remain unclear. To provide a foundation for the study of Culicoides-VSV interactions, C. sonorensis behavior, fitness related-traits, and patterns of viral infection were examined under various conditions. The research presented in this thesis shows that midges may become infected after ingesting blood meals (BM) containing doses as low as one infectious VSV particle per meal. Moreover, midge preference to feed on warmer BM at their first feeding may be an advantage for virus acquisition. Subsequent transmission can be efficiently achieved independent of the host body temperature without significantly impacting the vectors fitness. Likewise, ingestion of VSV in their first BM allows midges to ingest additional non-infectious meals, producing an infection enhancement and favoring transmission. After blood-feeding, most midges prefer to rest in areas with mild temperature, which maximizes their fitness and vectorial capacity. Investigating why some viruses spread from endemic regions to cause outbreaks in the U.S., results show that small genetic changes found in epidemic VSV lineages that appear to be related to host virulence also favor Culicoides vector competence. Lastly, this research show that female and male midges can venereally transmit VSV at significantly high rates, suggesting VSV maintenance in vector populations. This was the first demonstration of venereal transmission for VSV and for any of the viruses Culicoides midges transmit. This cumulative body of research highlights the epidemiological implications of vector behavior and physiology on VSV infection dynamics and provides fundamental knowledge in VSV transmission and maintenance mechanisms by C. sonorensis during outbreaks in the U.S.
Keywords: Midges; Culicoides; Vesicular stomatitis virus; Vector